Makhmalbaf at large : the making of a rebel filmmaker - Hamid Dabasho (London, 2008)
The name of Mohsen Makhmalbaf is almost synonymous with the dramatic rise of Iranian cinema in the aftermath of the Islamic Revolution, and over the last quarter of a century, his career as filmmaker and writer has reflected the tumultuous history of his homeland and the fate of its neighbours. Hamid Dabashi draws from his friendship with Makhmalbaf, as well as his direct involvement with Makhmalbaf's films and thought, to give us this deeply engaging book on the tumultuous life and spectacular career of a great filmmaker. This is also the account of Makhmalbaf's transformation, from committed Muslim revolutionary, who was jailed for his part in the revolution, into an artistic humanist of great energy and elegance. His films, including "The Peddler" and "The Time for Love", "Salaam Cinema", "Gabbeh", "Silence" and "Kandahar", confound conventional genres and are always surprising. They represent his own journey and take part in it, in ways that Dabashi explores with great insight. Makhmalbaf's cinematic career started in Iran and has since expanded into Turkey, Tajikistan, Afghanistan, Pakistan, India and into Europe. Dabashi uncovers how, moving across boundaries, Makhmalbaf's creative genius can illuminate our contemporary world. And this book is in part the story of a friendship. As Mohsen Makhmalbaf writes in its Preface: 'Hamid Dabashi - this pious atheist friend of mine, the man who loves cinema and hates art, this political activist who abhors politics, this thinking, pondering, critical intellect...I have learned much from him. Perhaps he too, has learned from me. The times he and I have spent together have been occasions of discovery and illumination.'